2023
DOI: 10.3390/polym15122645
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Attenuation Coefficients of Epoxy Resin with Carbopol Polymer as a Breast Phantom Material at Low Photon Energy Range

Abstract: Six different composites of epoxy resin and Carbopol 974p polymer were prepared based on Carbopol 974p polymer concentrations of 0%, 5%, 10%, 15%, 20%, and 25%. The linear and mass attenuation coefficients, Half Value Layer (HVL), and mean free path (MFP) of these composites were determined using single-beam photon transmission in the energy range between 16.65 keV and 25.21 keV. This was carried out by determining the attenuation of ka1 X-ray fluorescent (XRF) photons from niobium, molybdenum, palladium, silv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
0
0
Order By: Relevance
“…Nagaraja et al have investigated the gamma-shielding performances of polymers such as polystyrene, polypropylene, polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), and polychlorotrifluoroethylene (PCTFE) up to an energy of 1.330 MeV and found that PCTFE's radiation shielding property is superior to the others [11]. In another study, the photon absorption properties of epoxy resin with carbopol polymers, used in breast phantoms of different densities, were examined at low energies, and it was found that the density differences did not significantly affect the radiation permeability [12]. The radiation permeabilities of synthetic polymers, including polyethylene (PE), polystyrene (PS), polycarbonate (PC), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polyvinylpyrrolidone (PVP), polytetrafluoroethylene (PTFE), polypropylene (PP), and polymethyl methacrylate (PMMA), were investigated by Mirji et al between the energies of 14.4 and 1332 keV [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nagaraja et al have investigated the gamma-shielding performances of polymers such as polystyrene, polypropylene, polytetrafluoroethylene (PTFE), polyvinyl chloride (PVC), and polychlorotrifluoroethylene (PCTFE) up to an energy of 1.330 MeV and found that PCTFE's radiation shielding property is superior to the others [11]. In another study, the photon absorption properties of epoxy resin with carbopol polymers, used in breast phantoms of different densities, were examined at low energies, and it was found that the density differences did not significantly affect the radiation permeability [12]. The radiation permeabilities of synthetic polymers, including polyethylene (PE), polystyrene (PS), polycarbonate (PC), polyvinyl alcohol (PVA), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polyvinylpyrrolidone (PVP), polytetrafluoroethylene (PTFE), polypropylene (PP), and polymethyl methacrylate (PMMA), were investigated by Mirji et al between the energies of 14.4 and 1332 keV [13].…”
Section: Introductionmentioning
confidence: 99%